The Role of Thromboelastography in Heparin Therapy for COVID-19 Patients - Yosua Butar Butar; Yetti Hernaningsih; Narazah Mohd Yusoff (Faculty of Medicine Universitas Airlangga, 2022)
The 2019 coronavirus disease (COVID-19)-associated coagulopathy one of the significant complications often found in hospitalized COVID-19 patients. A hypercoagulable and prothrombotic state characterize coagulopathy with an increased risk of thrombotic events. Abnormal coagulation tests could predict bleeding risk, thrombosis, and disease severity. In addition to increasing the D-dimer, prolonged prothrombin time has decreased survival and increased treatment requirements. Based on laboratory findings, it was reported that 70% of patients with COVID-19 had disseminated intravascular coagulation (DIC) and 30% had thrombosis. Approximately 8% of patients with COVID-19 have hemorrhagic complications, the most common one is gastrointestinal bleeding. Variations in hypercoagulability and bleeding occur in COVID-19 patients. Therefore, the anticoagulant drug should be considered to minimize bleeding risk. An anti-bleeding agent for bleeding complications should be considered for the potential increase of coagulopathy. Thromboelastography (TEG) is a tool that is used to analyze the characteristics of viscoelastic clots, platelet function, and fibrinolysis in whole blood, providing a complete picture of the patient's coagulation status. From various therapeutic guidelines for COVID-19 patients, heparin is used as an anticoagulant drug to prevent thrombosis in COVID-19 patients. Starting from prophylactic doses to therapeutic doses, heparin is used to prevent the severity of COVID-19 patient course. The effect of coagulation on COVID-19 patients varies from no impact to hypercoagulation in TEG results.